Keunikan Jamaah dalam Merespon sebuah Konten Loyalitas Agen Travel Umrah Dimediasi oleh Kualitas Relasional - Evan Stiawan (Jurnal Pasar Modal dan Bisnis, 2020)
Purpose –The purpose of this study is to determine the effect of implicit self theory on the relational quality of pilgrims in choosing Umrah travel. Knowing the influence of relational quality on the loyalty of pilgrims in choosing Umrah travel. Knowing the effect of implicit self theory on the loyalty of pilgrims in choosing Umrah trave. Methods – Data analysis methods in the study used the Structural Equation Model (SEM) and Mediation Analysis methods. Finding – Based on the stages of analysis in accordance with existing research procedures, that according to the first objective to know the effect of implicit self theory on the relational quality of pilgrims in choosing Umrah travel, it can be concluded that it is influential. Knowing the influence of relational quality on the loyalty of pilgrims in choosing Umrah travel, it can be concluded that it is influential. Knowing the effect of implicit self theory on the loyalty of pilgrims in choosing Umrah travel, it can be concluded that it is influential. Implication -